The Impact of Marketing Through Instagram Social Media on Jiniso Product Purchasing Decision - Dian, Dian Rahayu; Harsoyo, Titik Desi (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to analyze the influence of advertising appeal, influencer marketing, and online customer reviews on purchasing decisions of Jiniso.id products on Instagram. The sample in this study consists of 100 respondents who have purchased Jiniso.id products online. The data collection technique used is a survey, with the research instrument being a questionnaire. The instrument test results indicate that the data in this study is proven to be valid and reliable. The classical assumption test states that the data in this study is normally distributed and produces a regression model free from multicollinearity and heteroscedasticity. The results of this study prove that advertising appeal has a positive and significant effect on purchasing decisions of Jiniso.id products on Instagram. Influencer marketing also has a positive and significant effect on purchasing decisions of Jiniso.id products on Instagram. However, online customer reviews do not have a positive and significant effect on purchasing decisions of Jiniso.id products on Instagram. These findings imply that further research should delve deeper into online customer reviews as an independent variable to achieve significant influence. The implications of this study for companies are to maintain and manage good online customer reviews to enhance consumer purchasing decisions.